2013
DOI: 10.1007/s13524-013-0223-3
|View full text |Cite|
|
Sign up to set email alerts
|

Perturbation Analysis of Indices of Lifespan Variability

Abstract: A number of indices exist to calculate lifespan variation, each with different underlying properties. Here we present new formulae for the response of seven of these indices to changes in the underlying mortality schedule (life disparity, the Gini coefficient, the standard deviation, the variance, Theil's index, the mean logarithmic deviation, and the inter-quartile range). We derive each of these indices from an absorbing Markov chain formulation of the life table, and use matrix calculus to obtain the sensit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
130
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 125 publications
(132 citation statements)
references
References 53 publications
1
130
0
1
Order By: Relevance
“…), and other measures of lifespan inequality correlate well with the s.d. [52]. We found that the s.d.…”
Section: (B) Senescencementioning
confidence: 74%
“…), and other measures of lifespan inequality correlate well with the s.d. [52]. We found that the s.d.…”
Section: (B) Senescencementioning
confidence: 74%
“…There is a large literature examining patterns of variation in the age at death and a variety of indices of discrepancy in longevity (Anand and Nanthikesan 2000;van Raalte and Caswell 2013). Like all life table calculations, these assume that all individuals experience the same set of specified vital rates, and hence the calculated variation is due to individual stochasticity (van Raalte and Caswell 2013).…”
Section: Individual Stochasticity and Its Componentsmentioning
confidence: 99%
“…The matrixŨ in (17) is the transient matrix of an absorbing Markov chain (Feichtinger 1971;Caswell 2001Caswell , 2006Caswell , 2009van Raalte and Caswell 2013). The transition matrix of this chain is…”
Section: The Absorbing Markov Chainmentioning
confidence: 99%
“…Many statistics of longevity can be obtained from the marginal fundamental matrix N * (e.g., Caswell 2001Caswell , 2006Caswell , 2009Caswell , 2013van Raalte and Caswell 2013;Engelman, Caswell, and Agree 2014). These statistics describe the marginal results for the cohort starting with the initial frailty distribution π(0), including:…”
Section: Longevity Variation and Disparitymentioning
confidence: 99%